Analisis Krisis Kebudayaan, Sosial Islam dan Implikasinya pada Pendidikan Masyarakat - Purwasih, Galuh Dwi (Proceedings of Annual Conference for Muslim Scholars, 2023)
One concept that is attracting a lot of attention in current discussions in our country is the concept of analysis of the Islamic social cultural crisis and its implications for public education. In doing good deeds, each region in the world has its own characteristics. These customs then experienced a mixture with Islamic traditions which ultimately created harmony without abandoning the applicable sharia. Acculturation of local culture with Islamic culture also occurs in Barongsawahan Village, Bandarkedungmulyo District, Jombang Regency, East Java. The people of Barongsawahan Village have a number of customs related to Islam which still survive to this day. Traditionally, residents hold an apem gerebeg before starting fasting, thousands of apem cakes are paraded to the Jombang city square and distributed to local residents. The apem cake is believed to be a symbol of asking for forgiveness from the Creator, that is not the only thing that attracts the residents of Barongsawahan village, some of them perform tarawih prayers at 21.00 - this is done by Muhammadiyah people and the tradition of eating together and visiting graves after the Eid prayer, the Id prayer itself was held in the Jayan Hamlet field, Bandar Kedungmulyo Village.